2008
DOI: 10.1111/j.1365-3059.2007.01806.x
|View full text |Cite
|
Sign up to set email alerts
|

Pythium myriotylum, a new pathogen of green beans in Spain

Abstract: In 2001 and 2002, bean plants ( Phaseolus vulgaris cvs Festival and Donna) cultivated on rockwool slabs in two commercial greenhouses in southeastern Spain were observed with root necrosis and necrotic streaks at the base of stems. In one greenhouse a few, scattered plants were affected, while in the other an estimated 20-30% dead plants occurred in distinct clusters. A Pythium sp. was consistently isolated from roots and stems of the affected plants on potato dextrose agar and cornmeal agar amended with pimar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Furthermore, studies have shown that the spread of Pythium myriotylum in ginger is strongly influenced by soil physic-chemical properties [16]. Specifically, changes in soil pH and organic matter content due to climate change can create a more favorable environment for the growth and survival of Pythium myriotylum [17].…”
Section: Climate Change and Pythium Myriothilummentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, studies have shown that the spread of Pythium myriotylum in ginger is strongly influenced by soil physic-chemical properties [16]. Specifically, changes in soil pH and organic matter content due to climate change can create a more favorable environment for the growth and survival of Pythium myriotylum [17].…”
Section: Climate Change and Pythium Myriothilummentioning
confidence: 99%
“…This expansion is characterized by its detection in regions previously considered unsuitable for its survival and proliferation. Recent report showed that P. myriotylum were detected in Shandong, Henan, and Anhu Province of China [2] which has average temperature in summer at 27 o C. Furthermore, the occurrence of P. myriothilum in crops such as hemp [32,33] and green bean [34] highlights its ability to infect a diverse range of plants and potentially cause widespread damage to agricultural systems. The accurate identification and understanding of Pythium species in agricultural environments are crucial for assessing their epidemiological implications.…”
Section: Epidemiological Implicationsmentioning
confidence: 99%